Tauhid Education in Surah Luqman Ayat 12-19 (Review of The Book of Tafsir Al Munir by Wahbah Az Zuhaili) - Aryan Nur Hafid; Anita Puji Astutik (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article discusses monotheistic education in Surah Luqman verses 12-19 explains teaching in children. This research was conducted by studying Surah Luqman. This type of research is included in library research (library research), researching library materials/literature related to research problems. The subject of this research is the Qur'an. At the same time, the object is the method of monotheistic education according to the Qur'an surah Luqman verses 12-19 in the perspective of tafsir Al-Munir by Wahbah Az-Zuhaili. Based on the research results in Surah Luqman verses 12-19 is an important role in building the growth of the fruit of the heart (child) by becoming an individual with great morals. Luqman made a solid educational foundation as the foundation of the existence of a Muslim in the form of monotheistic beliefs. Luqman warned his son not to use shirk to tarnish the monotheistic faith. Luqman even stated that shirk is a severe injustice. Luqman also instilled the respect given to his parents, who had cared for, taught, and even lovingly directed him. The need to treat both parents well is shown by setting the procedure to treat both parents well following the teachings of monotheism. Luqman instilled the piety of mahdhah in his social life, such as prayer and Amar ma'ruf nahi munkar, and adorned himself with noble morals and avoided low morals. Luqman's teachings are implemented with awareness of the power of Allah SWT and with love and affection, avoiding violence and coercion.